HUBUNGAN JENIS KEKERASAN MEKANIK DENGAN DERAJAT LUKA Studi Kasus Kekerasan Dalam Rumah Tangga di RS Bhayangkara Semarang Periode Januari–Desember 2024 - Naurah Nazhifah Dzatunnuha; Setyo Trisnadi (Jurnal Riset Multidisiplin Edukasi, 2026)
Domestic violence is a public health problem that continues to occur and causes physical and psychological impacts on victims. One of the most common forms of violence is mechanical violence, which can result in various degrees of injury. This study aimed to determine the relationship between types of mechanical violence and the degree of injury among domestic violence victims at Bhayangkara Hospital Semarang from January to December 2024. This study was an analytic observational study with a cross-sectional design. The sample consisted of all domestic violence victims examined and documented with visum et repertum during the study period. Data were collected from medical records and forensic reports. The variables analyzed were types of mechanical violence and degree of injury. Data analysis was conducted using Chi-Square test with significance level p<0.05. The results showed that most domestic violence victims experienced mechanical violence, with bruises and abrasions being the most common injuries. Most injuries were classified as minor injuries. Chi-Square analysis indicated a significant relationship between types of mechanical violence and degree of injury (p<0.05). In conclusion, there is a significant relationship between types of mechanical violence and degree of injury among domestic violence victims at Bhayangkara Hospital Semarang.